Criteria to evaluate effectiveness of creating consolidated group of taxpayers; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Khaperskaya A. V. Alena Vasilievna (2016, 2016)
Title screen